Nothing is perfect: the safety issues of integrase inhibitor regimens. Issue 6 (2nd June 2020) - Scévola, Sofía; Tiraboschi, Juan Manuel; Podzamczer, Daniel
ABSTRACT: Introduction: Since the administration of the first integrase strand transfer inhibitor (INSTI) in 2007, most international treatment guidelines consider INSTI-based regimens to be the preferred antiretroviral combinations for HIV-1-infected patients as a result of their safety and efficacy profile. INSTIs are generally well tolerated, and reported rates of discontinuation due to drug-related adverse events (AEs) have been very low to date. However, recent reports indicate that physicians should be aware of potential INSTI-related AEs to ensure good clinical practice. Areas covered: The authors performed a critical review of the safety issues affecting INSTIs based on published evidence from original studies and new data from researchers. Expert opinion: Almost all antiretroviral drugs, including INSTIs, are associated with undesirable AEs. Dolutegravir in particular has been associated with more frequent AEs such as neuropsychiatric disorders, neural tube defect in newborns, and weight gain. Data with bictegravir in routine practice are still scarce. While this association and its clinical relevance are not clear, physicians should be alert to the appearance of the aforementioned AEs and others in the future. In the meantime, INSTIs continue to be the preferred option in guidelines on antiretroviral therapy.